1993
DOI: 10.1021/ma00073a006
|View full text |Cite
|
Sign up to set email alerts
|

Interference of spinodal waves in thin polymer films

Abstract: We have studied the thickness dependence of the spinodal decomposition in thin films of a binary polymeric mixture. Nuclear reaction analysis (NRA) and time-of-flight forward recoil spectrometry (TOF-FRES) have been used to monitor the phase separation in thin films of poly(ethylenepropy1ene) (PEP) and perdeuterated poly(ethylenepropy1ene) (dPEP) after a quench into the two-phase region. The composition profiles are modeled by two distinct spinodal waves originating from the two surfaces of the films, and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
106
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(119 citation statements)
references
References 7 publications
10
106
1
Order By: Relevance
“…Coarsening is a ubiquitous natural phenomenon that occurs in a wide range of materials, such as metallic alloys [1][2][3][4][5][6][7][8], polymers [9][10][11][12][13][14][15], and semiconductors [16][17][18][19][20][21]. During coarsening, the total interfacial area of a microstructure decreases to reduce excess free energy associated with the existence of phase boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…Coarsening is a ubiquitous natural phenomenon that occurs in a wide range of materials, such as metallic alloys [1][2][3][4][5][6][7][8], polymers [9][10][11][12][13][14][15], and semiconductors [16][17][18][19][20][21]. During coarsening, the total interfacial area of a microstructure decreases to reduce excess free energy associated with the existence of phase boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, for polymer systems it has been found that confinement can change the glass transition temperature [1][2][3][4], molecular mobility [5,6], behaviour of the phases and morphology [7,8], molecular orientation [9] and crystallization behaviour [10][11][12][13]. Polymeric materials can be subjected either to chemical or to physical confinement.…”
Section: Introductionmentioning
confidence: 99%
“…the alignment of phase domains with respect to the patterned substrate (accompanied by free surface undulations), is the second main issue [19] discussed here. Selfassembly of polymer blends, cast as thin films on both homogeneous as well as patterned substrates, is a consequence of surface-directed phase separation [1,3,4,[9][10][11][12][13][23][24][25][26][27][28][29][30][31][32], discovered [23,27] only 10 years ago and described shortly below. Molecular mobility in the phase-separating films is promoted by the temperature elevated above glass transition (temperature quench applied for partly miscible or immiscible mixtures) or a common solvent added to the polymer blend (solvent quench encountered commonly for immiscible blends).…”
Section: Introductionmentioning
confidence: 99%